EEG based detection of alcoholics using spectral entropy with neural network classifiers - Padma Shri, T. K.; Sriraam, N. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/